ANTIOXIDANT ACTIVITY OF ESSENTIAL OIL AND CRUDE EXTRACTS FROM KAFFIR LIME LEAVES (CITRUS HYSTRIX) IN EAST BORNEO - Netty Maria Naibaho; Khusnul Khotimah (PROSIDING SEMINAR KIMIA, 2015)
Kaffir lime levaes is one of citrus cultivars in Indonesia that used as a food ingredient. The antioxidant activity of essential oil and crude extracts of Kaffir lime leaves in East Borneo was determined.The antioxidant potential of the samples was evaluated using two separate methods, inhibition of free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2-azino-bis 3ethylbenzothiazoline-6-sulphonic acid (ABTS).Results showed that the ethanol extracts were able to reduce the stable free radicals (DPPH and ABTS) with 49,5 μmol TE/mg and 42,8 μmol TE/mg, respectively.The total phenolic compounds were 4,06 μg GAE/mg. The essential oils from fresh leaves showed inhibition (DPPH) and (ABTS) at 5,78μmol TE/mg and 5,12μmol TE/mg, respectively. The strong antioxidant activity of the plant extracts may be attributed to the presence of phenolics.